Further delineation of van den Ende-Gupta syndrome: Genetic heterogeneity and overlap with congenital heart defects and skeletal malformations syndrome. - Hildebrandt, Clara C; Patel, Nisha; GrAHm, John M; Bamshad, Michael; Nickerson, Deborah A; White, Janson J; Marvin, Colby T; Miller, Danny E; Grand, Katheryn L; Sanchez-Lara, Pedro A; Schweitzer, Daniela; Al-Zaidan, Hamad I; et al. (Am J Med Genet A, 2021)
Van den Ende-Gupta syndrome (VDEGS) is a rare autosomal recessive condition characterized by distinctive facial and skeletal features, and in most affected persons, by biallelic pathogenic variants in SCARF2. We review the type and frequency of the clinical features in 36 reported individuals with features of VDEGS, 15 (42%) of whom had known pathogenic variants in SCARF2, 6 (16%) with negative SCARF2 testing, and 15 (42%) not tested. We also report three new individuals with pathogenic variants in SCARF2 and clinical features of VDEGS. Of the six persons without known pathogenic variants in SCARF2, three remain unsolved despite extensive genetic testing. Three were found to have pathogenic ABL1 variants using whole exome sequencing (WES) or whole genome sequencing (WGS). Their phenotype was consistent with the congenital heart disease and skeletal malformations syndrome (CHDSKM), which has been associated with ABL1 variants. Of the three unsolved cases, two were brothers who underwent WGS and targeted long-range sequencing of both SCARF2 and ABL1, and the third person who underwent WES and RNA sequencing for SCARF2. Because these affected individuals with classical features of VDEGS lacked a detectable pathogenic SCARF2 variant, genetic heterogeneity is likely. Our study shows the importance of performing genetic testing on individuals with the VDEGS "phenotype," either as a targeted gene analysis (SCARF2, ABL1) or WES/WGS. Additionally, individuals with the combination of arachnodactyly and blepharophimosis should undergo echocardiography while awaiting results of molecular testing due to the overlapping physical features of VDEGS and CHDSKM.

MN1 C-terminal truncation syndrome is a novel neurodevelopmental and craniofacial disorder with partial rhombencephalosynapsis. - Mak, Christopher C Y; Doherty, Dan; Lin, Angela E; Vegas, Nancy; Cho, Megan T; Viot, Géraldine; Dimartino, Clémantine; Weisfeld-Adams, James D; Lessel, Davor; Joss, Shelagh; Li, Chumei; Gonzaga-Jauregui, Claudia; et al. (Brain, 2020)
MN1 encodes a transcriptional co-regulator without homology to other proteins, previously implicated in acute myeloid leukaemia and development of the palate. Large deletions encompassing MN1 have been reported in individuals with variable neurodevelopmental anomalies and non-specific facial features. We identified a cluster of de novo truncating mutations in MN1 in a cohort of 23 individuals with strikingly similar dysmorphic facial features, especially midface hypoplasia, and intellectual disability with severe expressive language delay. Imaging revealed an atypical form of rhombencephalosynapsis, a distinctive brain malformation characterized by partial or complete loss of the cerebellar vermis with fusion of the cerebellar hemispheres, in 8/10 individuals. Rhombencephalosynapsis has no previously known definitive genetic or environmental causes. Other frequent features included perisylvian polymicrogyria, abnormal posterior clinoid processes and persistent trigeminal artery. MN1 is encoded by only two exons. All mutations, including the recurrent variant p.Arg1295* observed in 8/21 probands, fall in the terminal exon or the extreme 3' region of exon 1, and are therefore predicted to result in escape from nonsense-mediated mRNA decay. This was confirmed in fibroblasts from three individuals. We propose that the condition described here, MN1 C-terminal truncation (MCTT) syndrome, is not due to MN1 haploinsufficiency but rather is the result of dominantly acting C-terminally truncated MN1 protein. Our data show that MN1 plays a critical role in human craniofacial and brain development, and opens the door to understanding the biological mechanisms underlying rhombencephalosynapsis.
Keywords: Abnormalities, Multiple; Adolescent; Basilar Artery; Carotid Arteries; Cerebellar Vermis; Cerebellum; Child; Child, Preschool; Cohort Studies; Comparative Genomic Hybridization; Craniofacial Abnormalities; Female; Fibroblasts; Humans; Imaging, Three-Dimensional; Infant; Intellectual Disability; Language Development Disorders; Magnetic Resonance Imaging; Male; Middle Aged; Mutation; Nervous System Malformations; Nonsense Mediated mRNA Decay; Polymicrogyria; Real-Time Polymerase Chain Reaction; RNA-Seq; Syndrome; Tomography, X-Ray Computed; Trans-Activators; Tumor Suppressor Proteins; Whole Exome Sequencing; Whole Genome Sequencing

Mutations disrupting neuritogenesis genes confer risk for cerebral palsy. - Jin, Sheng Chih; Lewis, Sara A; Bakhtiari, Somayeh; Zeng, Xue; Sierant, Michael C; Shetty, Sheetal; Nordlie, Sandra M; Elie, Aureliane; Corbett, Mark A; Norton, Bethany Y; van Eyk, Clare L; Haider, Shozeb; et al. (Nat Genet, 2020)
In addition to commonly associated environmental factors, genomic factors may cause cerebral palsy. We performed whole-exome sequencing of 250 parent-offspring trios, and observed enrichment of damaging de novo mutations in cerebral palsy cases. Eight genes had multiple damaging de novo mutations; of these, two (TUBA1A and CTNNB1) met genome-wide significance. We identified two novel monogenic etiologies, FBXO31 and RHOB, and showed that the RHOB mutation enhances active-state Rho effector binding while the FBXO31 mutation diminishes cyclin D levels. Candidate cerebral palsy risk genes overlapped with neurodevelopmental disorder genes. Network analyses identified enrichment of Rho GTPase, extracellular matrix, focal adhesion and cytoskeleton pathways. Cerebral palsy risk genes in enriched pathways were shown to regulate neuromotor function in a Drosophila reverse genetics screen. We estimate that 14% of cases could be attributed to an excess of damaging de novo or recessive variants. These findings provide evidence for genetically mediated dysregulation of early neuronal connectivity in cerebral palsy.
Keywords: Animals; beta Catenin; Cerebral Palsy; Cyclin D; Cytoskeleton; Drosophila; Exome; Extracellular Matrix; F-Box Proteins; Female; Focal Adhesions; Genetic Predisposition to Disease; Genome, Human; Humans; Male; Mutation; Neurites; rhoB GTP-Binding Protein; Risk Factors; Sequence Analysis, DNA; Signal Transduction; Tubulin; Tumor Suppressor Proteins; Whole Exome Sequencing

SMCHD1 mutations associated with a rare muscular dystrophy can also cause isolated arhinia and Bosma arhinia microphthalmia syndrome. - Shaw, Natalie D; Brand, Harrison; Kupchinsky, Zachary A; Bengani, Hemant; Plummer, Lacey; Jones, Takako I; Erdin, Serkan; Williamson, Kathleen A; Rainger, Joe; Stortchevoi, Alexei; Samocha, Kaitlin; Currall, Benjamin B; et al. (Nat Genet, 2017)
Arhinia, or absence of the nose, is a rare malformation of unknown etiology that is often accompanied by ocular and reproductive defects. Sequencing of 40 people with arhinia revealed that 84% of probands harbor a missense mutation localized to a constrained region of SMCHD1 encompassing the ATPase domain. SMCHD1 mutations cause facioscapulohumeral muscular dystrophy type 2 (FSHD2) via a trans-acting loss-of-function epigenetic mechanism. We discovered shared mutations and comparable DNA hypomethylation patterning between these distinct disorders. CRISPR/Cas9-mediated alteration of smchd1 in zebrafish yielded arhinia-relevant phenotypes. Transcriptome and protein analyses in arhinia probands and controls showed no differences in SMCHD1 mRNA or protein abundance but revealed regulatory changes in genes and pathways associated with craniofacial patterning. Mutations in SMCHD1 thus contribute to distinct phenotypic spectra, from craniofacial malformation and reproductive disorders to muscular dystrophy, which we speculate to be consistent with oligogenic mechanisms resulting in pleiotropic outcomes.
Keywords: Adolescent; Child; Child, Preschool; Choanal Atresia; Chromosomal Proteins, Non-Histone; Female; Genetic Predisposition to Disease; Humans; Infant; Male; Microphthalmos; Muscular Dystrophies; Mutation; Nose; Phenotype